Ant Colony Optimization For Medical Image Analysis (International Journal of Environmental Sciences, 2025)
A set of characteristic parameters pertaining to the image will be the result of the various suggested image processing methods and algorithms that process images using mathematical notations and operations that can take on any natural form, such as a signal that needs to be processed. Some of the methods include image edge detection, image enhancement and restoration, and image segmentation. It is vitally important to use these processing techniques to analyze and extract important information from images processed by certain medical imaging techniques that depict the inside of a body.The data generated by these medical imaging procedures is utilized for pathology, diagnosis, clinical research, and therapeutic interventions. Medical imaging procedures are now an essential component of physiology and biomedical research. If the information obtained from these photos is compromised in any way, the non-tolerance remains.